The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s12041-012-0143-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of microsatellite loci in the Neotropical fish Astyanax altiparanae (Teleostei: Characiformes) and cross-species amplification

Abstract: . 2012 Isolation and characterization of microsatellite loci in the Neotropical fish Astyanax altiparanae (Teleostei: Characiformes) and cross-species amplification. J. Genet. 91, e24-e27. Online only: http://www.ias.ac.in/jgenet/OnlineResources/91/e24.pdf]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…These results are similar to those previously reported for these species (Leuzzi et al, 2004;Zaganini et al, 2012;Ferreira et al, 2015). Indeed, RAPD and microsatellite markers also revealed high levels of genetic diversity in populations of A. altiparanae from other drainages of the upper Paraná River basin, including the Grande River (H E = 0.799) (Zaganini et al, 2012), Paranapanema River (P = 72.65%) (Leuzzi et al, 2004), Tietê River, Keller River, and Pirapó River (Prioli et al, 2002). Similarly, high levels of genetic diversity were obtained for other species of the Astyanax genus, such as Astyanax bimaculatus in the Doce River basin, Brazil (Paiva et al, 2006), Astyanax scabripinnis in the Cambé stream, upper Paraná River, Brazil (Sofia et al, 2006), and Astyanax aff.…”
Section: Genetic Diversity and Demographic Analysessupporting
confidence: 93%
See 2 more Smart Citations
“…These results are similar to those previously reported for these species (Leuzzi et al, 2004;Zaganini et al, 2012;Ferreira et al, 2015). Indeed, RAPD and microsatellite markers also revealed high levels of genetic diversity in populations of A. altiparanae from other drainages of the upper Paraná River basin, including the Grande River (H E = 0.799) (Zaganini et al, 2012), Paranapanema River (P = 72.65%) (Leuzzi et al, 2004), Tietê River, Keller River, and Pirapó River (Prioli et al, 2002). Similarly, high levels of genetic diversity were obtained for other species of the Astyanax genus, such as Astyanax bimaculatus in the Doce River basin, Brazil (Paiva et al, 2006), Astyanax scabripinnis in the Cambé stream, upper Paraná River, Brazil (Sofia et al, 2006), and Astyanax aff.…”
Section: Genetic Diversity and Demographic Analysessupporting
confidence: 93%
“…Seven polymorphic loci were used for A. altiparanae; Asty15, Asty26, Asty23, Asty24, Asty04, Asty16, and Asty12 (Zaganini et al, 2012) and eight were used for G. brasiliensis; Gbra16, Gbra17, Gbra21, Gbra25, Gbra47, Gbra55, Gbra62, and Gbra63 . For A. altiparanae, 86 samples were used for genotyping (33 at UPE, 25 at MPE, and 28 at LPE), along with 82 G. brasiliensis samples (29 at UPE, 23 at MPE, and 30 at LPE).…”
Section: Microsatellite Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, microsatellites loci in closely related species have been identified. These include species belonging to the Anostomidae [163], Characidae [164,165], Cichlidae [166], Pimelodidae [167], Prochilodontidae [168][169][170] and Serrasalmidae [171] families.…”
Section: Next Generation Sequencing (Ngs) In Molecular Marker Discoverymentioning
confidence: 99%
“…In previous studies, microsatellites loci in closely related species have been identified. These include species belonging to the Anostomidae [163], Characidae [164,165] …”
mentioning
confidence: 99%